Representasi Kekerasan Fisik Pada Perempuan Dalam Video Klip Kesha Ratuliu Berjudul Tak Mau Berubah - Zatil Ismah, Susani; Santi Delliana, Anastasia (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Violence against women is often not considered a big problem or a social problem, because it is considered a household matter and other people do not need to intervene. Violence that occurs against women does not have to be physical violence but can destroy the basis of a person's life. This type of research is qualitative research. The purpose of this research is to find out the physical violence against women in the video clip of kesha Ratuliu entitled Don't want to change which is related to the three trichotomy concepts in Charles Sanders Peirce's Semiotic Theory. In this research data analysis using descriptive qualitative method using Charles Sanders Peirce Semiotics analysis, there are three concepts in analyzing, namely: 1. Sign or representation 2. Object 3. Interpretant. The results of this study are the interpretation of signs or meanings in Kesha Ratuliu's video clip entitled Tak Mau Change by using Charles Sanders Peirce's semiotic analysis, namely: 1) Physical violence against women in the video clip 2) The psychological impact of physical violence.